KINERJA PEGAWAI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA BATAM DALAM MENYELENGGARAKAN PELAYANAN PUBLIK - Manalu, Rugun Josepita; Abbas, Azhar (SCIENTIA JOURNAL, 2019)
This study aims to determine employee performance and employee performance factors in the Batam City Population and Civil Registry Service. This type of research is descriptive qualitative, that is describing or describing all events obtained in the field and for solving problems that exist based on data. Data collection is carried out through interviews directly to speakers and observations in the field. The sources of this research were the Head of the Civil Registration Service Division, the Birth Certificate, Employee or Staff and the service user community at Disduk and Capil in Batam City. From the results of this study, overall Employee Performance Disduk and Capil of Batam City are not good enough in providing services. Judging from the indicators of organizational performance measurement, which includes Productivity, Service Quality, Response, Responsibility, and Accountability. It is evidenced by the lack of Human Resources that do not support Disduk and Civil Registry Employee Performance in Batam City in dealing with the high demand for the production of birth certificates reinforced by conditions that are not sufficiently adequate. In terms of productivity employees can be said to be less qualified because of some placement of employees who do not match their expertise.